Asynchronous Transfer Mode (ATM) Congestion Control Techniques and Applications in Communication and Data Network Systems - Saverio Mascolo; Mario Gerla (Database and Data Communication Network Systems Techniques and Applications, 2002)
Flow and congestion control is a major research issue in high-speed-communication data networks. Link propagation delays with higher transmission speed, increases the bandwidth-delay product, and has an adverse impact on the stability of closed-loop control algorithms. The growth of data traffic along with the ever-increasing demand of quality of service requires more sophisticated congestion-control techniques to manage the sharing of the network resources. This chapter proposes a classical control theory as a simple and powerful tool for tackling the issue of congestion control in high-speed-communication networks. It also proposes the Smith principle for designing a congestion-control algorithm for high-speed asynchronous transfer mode (ATM) data networks. The dynamics of the controlled data networks are analyzed using standard Laplace transform techniques. Finally, the advantages of the proposed algorithm in comparison to a popular explicit-rate-indication algorithm are discussed and computer simulations are also carried out.